Congratulations! funding from Fundamental Research Grant Scheme (FRGS) 2023 - UiTM, Arshad Ayub Graduate Business School (Arshad Ayub Graduate Business School, 2023)
Congratulations to Assoc. Prof. Dr. Wahida Ahmad (Project Leader), Dr. Nur Hazimah Amran, Assoc. Prof. Dr. Herwina Rosnan, Assoc. Prof. Dr. Khaw Lee Hwei, and Dr. Rafisah Mat Radzi for successfully securing funding under the Fundamental Research Grant Scheme (FRGS) 2023 for their research project titled “Modelling Financial Scam Detection with the Fusion of Financial Knowledge and Financial Wellbeing: The Big Five Taxonomy of Personality Traits” with the amount of RM109,000.00.